Third International Workshop on Variability Modelling of Software-intensive Systems. Proceedings - David Benavides; Andreas Metzger; Ulrich Eisenecker (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2009)
This ICB Research Report constitutes the proceedings of the Third International Workshop on Variability Modelling of Software-intensive Systems (VaMoS'09), which was held from January 28-30, 2009 at the University of Sevilla, Spain.
Keywords: 650; Wirtschaftsinformatik; Softwareentwicklung